SOLVING RESEARCH PROBLEMS OF FLOWS IN CHANNELS USING NUMERICAL METHODS (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
The study of fluid flow in channels is fundamental in various fields of engineering and environmental sciences. Traditional analytical methods often fall short in handling complex geometries and varying boundary conditions. Numerical methods have thus become indispensable in understanding and predicting fluid dynamics in channels. This paper explores the application of numerical methods in the study of flows in channels, focusing on the Finite Difference Method (FDM), Finite Element Method (FEM), and Computational Fluid Dynamics (CFD). Case studies and simulations are presented to illustrate the effectiveness of these methods in solving real-world problems.